How Complementary Are Prudential Regulation and Monetary Policy? - Canuto, Otaviano (World Bank, Washington, DC, 2012)
Could either monetary policy or financial prudential regulation be relied on individually to mitigate asset price cycles or their effects? If both ways are effective, monetary policy and prudential regulation could then be considered 'substitutes,' in the sense that the individual use of either instrument leads to a reduction in the volatility of both corresponding targets. This note, however, argues in favor of complementarily rather than substitution in the use of monetary and macro-prudential policies: the combined (articulate) use of both policies tends to be more effective than a standalone implementation of either.